2016
DOI: 10.1038/srep20337
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of multiple metastable polytypes in rhombohedral bismuth

Abstract: Derivative structural polytypes coexisting with the rhombohedral A7 structure of elemental bismuth (Bi) have been discovered at ambient condition, based on microstructure analyses of pure Bi samples treated under high pressure and high temperature conditions. Three structures with atomic positions close to those of the A7 structure have been identified through first-principles calculations, showing these polytypes energetically comparable to the A7 structure under ambient condition. Simulated diffraction data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…In the 30 × 30-nm 2 area shown in Fig. S8, numerous domains of various polytypes are observed that have close similarity to the A-7 structure (38). Crystal lattice varies smoothly across the domains with poorly defined domain boundaries.…”
Section: Physicsmentioning
confidence: 94%
“…In the 30 × 30-nm 2 area shown in Fig. S8, numerous domains of various polytypes are observed that have close similarity to the A-7 structure (38). Crystal lattice varies smoothly across the domains with poorly defined domain boundaries.…”
Section: Physicsmentioning
confidence: 94%
“…166, Rtrue3¯m). 49,50 That structure comes from the transformation of simple cubic structure via two separate distortions including trigonal shear and relative displacement 51‐53 . Moreover, mosaic structures of Bi consisted of one monoclinic (M) and two triclinic structures (T1 and T2) 54 . They might be formed through the tiny lattice distortion of A7 structure and they coexist with the A7 structure 55 .…”
Section: Structural Of Bismuth‐based Photocatalytic Materialsmentioning
confidence: 99%
“…2 (Ptrue1¯), and No. 2 (P1) in space groups were assigned to A7, M, T1, and T2 structures, respectively 54,56,57 . The unique electronic band feature of Bi is the existence of a small overlap between conduction band at the L points of the Brillouin zone and valence band at the T points (T and L points would have been equivalent in nondistorted f.c.c lattice).…”
Section: Structural Of Bismuth‐based Photocatalytic Materialsmentioning
confidence: 99%
“…Under ambient condition, Bi is commonly designated as a rhombohedral lattice (space group R-3m, so-called arsenic or A7 structure), which is characterized by a pair of atoms spaced non-equidistantly along the trigonal axis in a Peierls distortion of the simple cubic structure 47,48 . Alternatively, the structure of Bi can be described as a hexagonal lattice with six atoms per unit cell, or as a pseudo-cubic structure with one atom per unit cell 49 .…”
Section: Crystal Growth and Characterizationmentioning
confidence: 99%